COLORIMETRIC FLOW-INJECTION ANALYSIS OF DISSOLVED IRON IN HIGH DOC WATERS - Pullin M.J.; Cabaniss S.E. (My University, 2001)
An iron flow-injection analysis system has been optimized for the analysis of iron in waters high in dissolved organic carbon. The method detects either dissolved iron(II) or total dissolved iron with a detection limit of 10nM, precision of 0.65% at 1μM, and a dynamic range of four orders of magnitude. There are minimal interferences (<1%) from other metals at environmental concentrations. The iron(II) method measures iron(II) in the presence of excess iron(III) with less than 1% interference. When used with pre-acidified samples, the total dissolved iron method agrees well with electrothermal atomic absorption spectrometry for a variety of natural waters with a range of dissolved organic carbon (3-36mgC/L) and iron (1-28μM) concentrations. When used with samples at their ambient pH, the total dissolved iron method detects dissolved iron, but not colloidal iron (size fraction 0.05-0.45μm).
Keywords: IRON; FLOW-INJECTION ANALYSIS; FERROZINE; COLLOID; REDOX; FRESH WATER